Strategic cooperation of electric power systems of Russia and Central Asia for the creation of common Eurasian electric power space - Chudinova Lyudmila; Podkovalnikov Sergei (E3S Web of Conferences, 2019)
The paper considers electric power integration projects realized and to be implemented on the territory of Eurasia, that include Russia and countries of Central Asia, neighboring regions of Caucasus, South Asia, and others. Studies are focused on the effectiveness of electric power integration of electric power systems of Russia and Central Asia in the long-term perspective, with account of electric ties with neighboring countries.